2011
DOI: 10.1001/archophthalmol.2011.8
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Plasmin Without Vitrectomy for Macular Edema Secondary to Branch Retinal Vein Occlusion

Abstract: To evaluate the effects and safety of intravitreal injections of autologous plasmin enzyme (APE), without vitrectomy, as a treatment for macular edema secondary to branch retinal vein occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Several previous studies [12]–[17] determined that optical coherence tomography can help in the evaluation of macular edema in diabetic or non-diabetic patients, and also help in the follow-up of the patients during treatment to establish quantitative or qualitative responses to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies [12]–[17] determined that optical coherence tomography can help in the evaluation of macular edema in diabetic or non-diabetic patients, and also help in the follow-up of the patients during treatment to establish quantitative or qualitative responses to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…One comparative study reported significantly higher visual acuities at 1 year follow-up in patients with DME treated with APE compared with those not receiving such treatment 134. More recently, a small prospective study found that intravitreal APE without vitrectomy improved central macular thickness and visual acuity in eyes with macular edema complicating branch RVO 137. Of note, many groups reported varying degrees of vitreous liquefaction following APE administration,77,127,131,133,135,136 although several others either did not comment or noted the lack of liquefaction 134.…”
Section: Vitreolytic Agentsmentioning
confidence: 99%
“…Sakuma et al17 and Udaondo et al18 evaluated the effects and safety of intravitreal injections of APE, without vitrectomy, as a treatment for macular edema secondary to branch retinal vein occlusion and reported that IAP improves CMT and BCVA and may be a safe and effective alternative therapy for this condition.…”
Section: Discussionmentioning
confidence: 99%